2022
DOI: 10.7189/jogh.12.05028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety, and stress among first responders for medical emergencies during COVID-19 pandemic: A meta-analysis

Abstract: Background The COVID-19 pandemic has been shown to cause enormous psychological burden among health care workers, including first responders. However, psychological well-being of first responders, essential in the fight against COVID-19 pandemic, has often been ignored. We performed the first meta-analysis to explore the prevalence of 1) depression, 2) anxiety, and 3) stress among first responders for medical emergencies during the COVID-19 pandemic. Methods A comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
(48 reference statements)
0
20
3
Order By: Relevance
“…[ 2 , 5 , 6 , 7 , 9 , 11 , 22 , 23 , 26 , 58 , 60 ] contradict our findings, as they showed that the main sources of anxiety among health professionals were due to patient care, concern about becoming infected or infecting family members, work-related concerns, burnout, and fear of the unknown. Our results are inconsistent with [ 2 , 5 , 6 , 11 , 16 , 19 , 20 , 22 , 23 , 26 , 36 ], that reflected that the COVID-19 pandemic has generated higher levels of anxiety among health workers, regarding factors such as having been in contact with the virus or fear at work. Moreover, our results are contrary to the studies by [ 18 , 60 ], as they showed that health professionals have had to develop their profession in a precarious environment, putting both their individual and collective health at risk, considerably increasing their patients’ death anxiety; the predictor variables of this anxiety are the absence of personal protective equipment and high levels of burnout, emotional exhaustion, and depersonalization.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…[ 2 , 5 , 6 , 7 , 9 , 11 , 22 , 23 , 26 , 58 , 60 ] contradict our findings, as they showed that the main sources of anxiety among health professionals were due to patient care, concern about becoming infected or infecting family members, work-related concerns, burnout, and fear of the unknown. Our results are inconsistent with [ 2 , 5 , 6 , 11 , 16 , 19 , 20 , 22 , 23 , 26 , 36 ], that reflected that the COVID-19 pandemic has generated higher levels of anxiety among health workers, regarding factors such as having been in contact with the virus or fear at work. Moreover, our results are contrary to the studies by [ 18 , 60 ], as they showed that health professionals have had to develop their profession in a precarious environment, putting both their individual and collective health at risk, considerably increasing their patients’ death anxiety; the predictor variables of this anxiety are the absence of personal protective equipment and high levels of burnout, emotional exhaustion, and depersonalization.…”
Section: Discussioncontrasting
confidence: 99%
“…Health professionals perceived that their psychological health worsened during the COVID-19 pandemic, and higher levels of anxiety were associated with increased avoidance coping strategies [ 7 , 14 , 17 , 41 , 45 , 50 , 57 ]. Thus, people with high levels of anxiety symptoms were prone to a maladaptive response to uncertain new situations [ 1 , 9 , 16 , 17 , 35 , 39 , 40 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic's scarce protective resources and increased workload may have also had an impact on them. Therefore, providing work resources (such as protective gear) to ensure and enhance first responders' safety may eventually result in higher psychological well-being and prehospital medical service delivery [ 51 ].…”
Section: Discussionmentioning
confidence: 99%